Editor-in-chief’s note: Women in the family and society - Navabinejad, Shokouh (Applied Family Therapy Journal (AFTJ), 2022)
As half of the population, women play a very important and vital role in the mental health of the family and society. Women have broad and multifaceted existential dimensions, and in various roles of motherhood, wife, upbringing, moral, social, and management, they have shown countless abilities and capabilities in fulfilling their responsibilities. Therefore, considering the sensitive role of women in the health and success of a family and, ultimately, the dynamics of a society, special attention should be paid to their physical, psychological, emotional, social, and spiritual needs, and adequate attention should be given to providing these needs. A woman is a symbol of affection, love, and sacrifice and the main focus of the family center. The manifestation of these characteristics is understood in the sacred role of motherhood. The mother is not only the transmitter of culture, customs, social behavior, and moral and religious values from one generation to another; It is also a reviving and protecting culture and desirable values of the society. Therefore, many times in ancient Iranian literature, songs praising women and mothers have been mentioned, and Ferdowsi, the great poet of Iran, has given a place to women and mothers beyond child rearing and love for the wife, and that is respect for the mother’s wisdom. This type of view of women can rarely be found in literary and historical texts of the world. However, more attention should be paid to the serious presence of women as one of the most important pillars of development. Achieving the goals of development of thought and serious action to meet the human needs of people, especially women, and it is necessary to make necessary plans to properly organize the status of women, empower them and pay attention to their interests and contribution in the development of society. Undoubtedly, today, one of the indicators of the degree of development of any country is the level of participation in the role that women are responsible for. Many women in our society are compassionate about the fate of society in their country through social participation and feel responsible. We thank God for giving us the success of publishing a collection of articles focusing on "women" in the winter issue of 2023 of the "Applied Family Therapy" journal to fulfill our massive cultural mission in connection with the publication of research findings and scientific excerpts in the framework of the system’s spiritual and desirable values in the women’s field.